Pengaruh Internal Capital Adequency Ratio (CAR), Financing To Deposit Ratio (FDR), dan Biaya Operasional Per Pendapatan Operasional (BOPO) dalam Peningkatan Profitabilitas Industri Bank Syariah di Indonesia - Hakiim, Ningsukma; Rafsanjani, Haqiqi (Universitas Brawijaya, Indonesia, 2016)
The aims of this study are to determine and analyze the influence of health bank ratio as measured by CAR, FDR, and ROA to the profitability of Islamic Banks industry in Indonesia. The data use in this research is secondary data include capital adequacy ratio (CAR), liquidity (FDR), operational efficiency (ROA) and profitability (ROA) in Islamic commercial banking industry registered at Bank Indonesia. The data is time series cross section during the year 2010-2012 and 2013 (only in January to March 2013) obtained from the official website of banking statistics, Bank Indonesia (www.bi.go.id). Data analysis used linear regression models with SPSS 16. From the observation and data analysis, the finding shows that CAR, FDR, and ROA to ROA are the indicator of the health Bank to measure profitability has a high relationship. CAR partially has no significant effect on profitability. FDR variable partially has a negative effect and has no significant effect on profitability. In the other hand, BOPO partially has a significant negative effect on ROA.